Bending Properties of Fiber-Reinforced Composites Retainers Bonded with Spot-Composite Coverage. (10th October 2017) - Sfondrini, Maria Francesca; Gandini, Paola; Tessera, Paola; Vallittu, Pekka K.; Lassila, Lippo; Scribante, Andrea
Abstract : Orthodontic and periodontal splints are prepared with round or flat metallic wires. As these devices cannot be used in patients with allergy to metals or with aesthetic demands, fiber-reinforced composite (FRC) retainers have been introduced. Stiffness of FRC materials could reduce physiologic tooth movement. In order to lower rigidity of conventional FRC retainers, a modified construction technique that provided a partial (spot) composite coverage of the fiber has been tested and compared with metallic splints and full-bonded FRCs. Flat (Bond-a-Braid, Reliance Orthodontic Products) and round (Penta-one 0155, Masel Orthodontics) stainless steel splints, conventional FRC splints, and experimental spot-bonded FRC retainers (Everstick Ortho, StickTech) were investigated. The strength to bend the retainers at 0.1 mm deflection and at maximum load was measured with a modified Frasaco model. No significant differences were reported among load values of stainless steel wires and experimental spot-bonded FRC retainers at 0.1 mm deflection. Higher strength values were recoded for conventional full-bonded FRCs. At maximum load no significant differences were reported between metallic splints (flat and round) and experimental spot-bonded FRCs, and no significant differences were reported between spot- and full-bonded FRC splints. These results encourage further tests in order to evaluate clinical applications of experimental spot-bonded FRC retainers.